Corrosion behaviour and protection of copper and aluminium alloys in seawater (Woodhead Publishing in materials, 2007)
Copper and aluminium alloys are widely used in marine engineering in areas such as pipelines, storage tanks, ships' hulls and cladding for offshore structures. This important book reviews key factors affecting the corrosion and service life of these materials in the marine environment. The book is divided into five parts, with part one reviewing key aspects of the corrosion behaviour of both these alloys. Part two discusses the use of copper and copper-nickel alloys in seawater, whilst Parts 3 and 4 cover aluminium bronzes and alloys. The final section of the book covers the use of aluminium-based materials as anodes for the cathodic protection of marine structures. Corrosion behaviour and protection of copper and aluminium alloys in seawater is an important reference for marine engineers concerned with the corrosion and service life of these materials. Reviews key factors affecting the corrosion and service life of copper and aluminium alloysDiscusses the use of the alloys in seawater